Technical Literacy and Standardization of Indonesian Electrical Terms Based on SNI (Indonesian National Standard) - Ikram Haidar Hilmi; Muhamad Panji Prasetya; Muhammad Gilang Abyan; Muhammad Ihsan Rafiqi Hailan (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The development of electrical systems in Indonesia requires not only technological advancement but also the standardization of technical terminology to improve communication accuracy and occupational safety. This study aimed to analyze the level of technical literacy and the implementation of Indonesian National Standard (SNI)-based electrical terminology among students, workers, and the general public. The research employed a quantitative descriptive method with a survey approach. The population consisted of individuals involved in educational and technical environments, with 53 respondents selected through purposive sampling. Data were collected using an online questionnaire covering understanding of SNI, perceptions of standard terminology, and frequency of using PUIL/SNI documents. The data were analyzed using descriptive statistical techniques through frequency and percentage distribution. The findings revealed that most respondents understood the importance of standardized electrical terminology, particularly regarding cable color uniformity and the replacement of non-standard market terms. However, the use of PUIL/SNI documents was still inconsistent, indicating a gap between awareness and practical implementation. The study concludes that strengthening technical literacy through education, training, and consistent application of SNI terminology is essential to improve technical communication, installation quality, and occupational safety in the electrical sector in Indonesia